First report of serological, molecular detection, and characterization of human parvovirus B19 infections among sickle cell anaemia patients in Khartoum State, Sudan - Khalid, Salman (2025)
BackgroundPatients with haematological disorders, such as sickle cell anaemia, are at an elevated risk of transient aplastic crisis due to parvovirus B19 infection. The virus targets specific integration sites in the human genome, disrupting cellular division. However, the molecular mechanisms of infection remain poorly understood. AimThis study aimed to determine the prevalence of human parvovirus B19 among patients with sickle cell anaemia in Khartoum State, Sudan. MethodsNinety patients (aged <5 to >15 years) with sickle cell disease attending Gaafer Ibnouaf Children’s Hospital between November 2016 and February 2017 were recruited. Sera and plasma samples were analyzed. IgG and IgM antibodies were measured using ELISA, and viral DNA was detected in plasma using nested-PCR. Phylogenetic analysis of sequenced B19 strains focused on the overlapping region of the minor (VP1) and major (VP2) capsid protein genes. ResultsAnti-parvovirus B19 IgG antibodies were detected in 57 of 90 patients (63.3 %), while IgM antibodies were present in 7 (7.8 %). Viral DNA was identified in 23 (25.5 %) patients. Among the 23 DNA-positive patients, 7 (30 %) were seronegative for both IgG and IgM antibodies, highlighting the importance of molecular diagnostics in identifying active infections, especially in early stages. Children under 5 years of age exhibited a higher nucleic acid detection rate compared to older age groups, suggesting the importance of molecular testing in younger patients particularly in the early detection of Parvovirus B19 during the acute phase of infection, before the body has developed detectable antibodies and also in immunocompromised children, who may not mount an antibody response detectable by serological methods. Phylogenetic analysis revealed two distinct Sudanese clusters: one (50 % of sequences) formed a unique clade with low similarity to existing genotypes, while the other (50 %) closely resembled genotype 1 A sequences from Iraq, Iran, and Tanzania. ConclusionParvovirus B19 antibodies and DNA were detected at high prevalence among Sudanese children with sickle cell anaemia. Screening for parvovirus B19 is critical for patients requiring blood transfusions, particularly those with haematological disorders. This study provides the first report of parvovirus B19 detection, sequencing, and characterization among Sudanese patients with sickle cell anaemia.